2020
DOI: 10.7150/ijbs.41637
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes in osteoarthritis and cartilage injury: advanced development and potential therapeutic strategies

Abstract: Articular cartilage injury is a common clinical problem, which can lead to joint dysfunction, significant pain, and secondary osteoarthritis (OA) in which major surgical procedures are mandatory for treatment. Exosomes, as endosome-derived membrane-bound vesicles, participating in intercellular communications in both physiological and pathophysiological conditions, have been attached great importance in many fields. Recently, the significance of exosomes in the development of OA has been gradually concerned, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 72 publications
(95 reference statements)
0
21
0
Order By: Relevance
“…Synovial fluid can be monitored to assess pathophysiological alterations in the knee joint space, as it is closely associated with the articular cartilage and the synovial membrane in this tissue site 32 , 33 . Cell-derived exosomes represent particularly promising tools for diagnostic biomarker identification when evaluating disease progression, as they can both reflect and influence pathophysiological conditions within a given microenvironmental setting 34 , 35 . Herein, we, therefore, conducted an analysis of miRNAs within exosomes derived from the synovial fluid of OA and control patients.…”
Section: Discussionmentioning
confidence: 99%
“…Synovial fluid can be monitored to assess pathophysiological alterations in the knee joint space, as it is closely associated with the articular cartilage and the synovial membrane in this tissue site 32 , 33 . Cell-derived exosomes represent particularly promising tools for diagnostic biomarker identification when evaluating disease progression, as they can both reflect and influence pathophysiological conditions within a given microenvironmental setting 34 , 35 . Herein, we, therefore, conducted an analysis of miRNAs within exosomes derived from the synovial fluid of OA and control patients.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have confirmed that EVs from patients with an osteoarthritic joint were significantly different from normal patients (Barile and Vassalli, 2017 ; Zhang et al, 2017 ; Zhou Q. et al, 2020 ) ( Figure 3 ). For instance, significantly elevated concentrations of LncRNA PCGEM1 were detected in synovial fluid from patients with OA (Zhao and Xu, 2018 ).…”
Section: Changes In Evs To Reflect the Joint Diseasementioning
confidence: 82%
“…In this aspect, MSC-derived exosomes have proven to be valuable as they can exert an anti-inflammatory response. For example, adipose MSC-derived exosomes could decrease levels of pro-inflammatory mediators, reducing stimulation of NF-κB and activator protein 1 while increasing expression of anti-inflammatory cytokines and the expression of miR-100-5p, which binds to 3 UTR of mTOR to augment autophagy activity [8,111]. With similar mechanisms, exosomes isolated from bone marrow-derived MSCs [112] and umbilical-cord-derived MSCs [113] were able to relieve the pathological Pharmaceuticals 2021, 14, 1093 9 of 25 characteristics in diseased joints through decreasing the infiltration of inflammatory cells as well as repressing levels of inflammatory factors [114].…”
Section: Promoting Cartilage Repair Using Exosomesmentioning
confidence: 99%
“…In particular, exosomes, a type of small extracellular vesicle (EV) secreted by cells for intercellular communication, have become the focus of recent studies. Exosomes are rich in proteins, lipids, and nucleic acids and have been documented to promote cartilage regeneration [7,8]. Previously, a battery of miRNAs was found to be involved in cartilage regeneration [9][10][11].…”
Section: Introductionmentioning
confidence: 99%